Історичний аналіз інтродукції рослин і наукової діяльності: до 70-річчя ботаніко-географічної ділянки “Степи України” у Національному ботанічному саду імені М.М. Гришка НАН України - Gritsenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – analyze the history of plant introductions and scientific activities in the botanical and geographical plot “Steppes of Ukraine” in M.M. Gryshko National Botanical Garden of the NAS of Ukraine for 70 years (1949–2019); highlight certain periods, establish their features. Material and methods. The studies were conducted in 2015–2019. Processed and analyzed literary sources, reports and manuscripts that are relevant to the botanical and geographical plot “Steppes of Ukraine”. Results. In 1949–1969 in the botanical and geographical plot “Steppes of Ukraine”, for the first time, most species of steppe plants were introduced. In 1970–1990 investigated the biology, morphology, ornamental and medicinal qualities, ontogenesis of the introduced plants. Since 1991 the study of introduced populations of rare and endangered plant species has begun. In 2001–2019 introduction included the enrichment of the collection with new species, the replenishment of the number of individuals and the restoration of the lost rare species. Scientific activity has become intense. Various comprehensive studies were carried out – vegetation cover of the plot, introduction coenopopulations and the results of the introduction of plants, phytodiversity and other aspects. Conclusions. In the history of plant introductions and scientific activities in the botanical and geographical plot “Steppes of Ukraine” for 70 years, four periods are distinguished: I (1949–1969) – large-scale, intensive primary introduction of most steppe plant species, II (1970–1990) – research of the biology, morphology, ontogenesis of the introduced plants, III (1991–2000) – the study of introduction populations of rare and endangered plant species, IV (2001–2019) – enrichment and replenishment of the collection of introduced plants, restoration of lost rare species; intensive scientific activity, various comprehensive researches.